FORMING OF STEADY MOTIVATION AND ORIENTATION OFENTRANTS IN THE SYSTEM OF HIGH PROFESSIONAL SCHOOLS IN KAZAKHSTAN - Lekerova, Gulsim Janabergenovna; Issabaeva, Aiman Sagintaevna; Issabekova, Azhar Ordabaevna; Bahramova, Gulmira Abdurasulovna; Torehanovich, Balabekov Aidarhan; Demeuov, Ahan Kalybaevich (European Scientific Journal, ESJ, 2015)
The research of psychological bases of the formation and the development of professional pedagogical activity becomes very urgent direction of psycho-pedagogical researches nowadays, since the knowledge and understanding of motivational sphere of any specialist allows to develop his professional self-determination, as on the level of choosing a profession, so in the process of his perfection as a professional. In the process of professionalization of a teacher some changes in his motivational sphere are occurring, which can lead not only to his pedagogical mastering improvement, but also to a significant personal growth. The scientific novelty of the research is defined by the fact that in pedagogical psychology on the experimental-psychological basis the system of productive teaching of students is worked out at the first time, which allows increasing considerably the effectiveness of teaching on the basis of educational system’s motivational processes management.